(3EOGQI hXjaI GdEMJjGLGJ (B:s (3aj GdefXeGJ GdeYGUQI eONd ESJQGJjLj dJMbjb GdejRI GdJfGaSjI (B/s - (3CHh HcQ, eUWaj eMehOs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s)
(3GdEWGQ GdYGe dEOGQI hXjaI GdEMJjGLGJ(B-(3bQGQ JhajQ GdEMJjGLGJ(B((3Gdeaghe,GdNUGFU,GdCQcGf(B)(3GdEWGQ GdJfXjej hGdEOGQj dhXjaI GdEMJjGLGJ(B-(3GdJacjQ hGdJNWjW GdESJQGJjLj aj hXjaI GdEMJjGLGJs
Keywords: (3GdGOGQIs; (3GdefGaSIs; (3GdefXeGJs